2015
DOI: 10.15218/zjms.2015.0018
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity of essential oils from local plants against fluconazole-resistant oral Candida albicans isolates

Abstract: Background and objective: Candida albicans is an oral commensal flora that causes opportunistic local and systemic infections in immunocompromied individuals. Fluconazole is frequently used for treating patients with active infections or preventing recurrent infections. The emergence of resistant strains encouraged scientists to search for compounds that have antifungal property and can overcome the usual microbial resistant mechanisms to antimicrobial agents. Essential oils from natural plants have received g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In a previous study by Abdulaziz et al [ 18 ], the diameters were higher in thyme essential oil (42.4±6.5) in comparison with rosemary essential oil (11.8±2.8). The serial two-fold dilutions of the tested essential oils showed that both oils exhibited antifungal activities even at very low concentrations.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study by Abdulaziz et al [ 18 ], the diameters were higher in thyme essential oil (42.4±6.5) in comparison with rosemary essential oil (11.8±2.8). The serial two-fold dilutions of the tested essential oils showed that both oils exhibited antifungal activities even at very low concentrations.…”
Section: Discussionmentioning
confidence: 81%
“…However, Sepehri et al [ 27 ] obtained results that supported the findings of this study while carrying out sensitivity test of essential oils from eucalyptus. Similarities of the test pathogens could be a contributing factor [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…officinalis essential oil showed the greatest antioxidant activity with an IC50 of 2.6 mg/L. In a previous study by Abdulaziz et al (2015) (35) , the diameter of inhibition zone with rosemary essential oil was (11.8±2.8) and the serial two-fold dilutions of the tested essential oil showed exhibited antifungal activities even at very low concentrations. In a study by…”
Section: (Dpph) Radical Scavenging Methodsmentioning
confidence: 75%